2020
DOI: 10.1002/brb3.1855
|View full text |Cite
|
Sign up to set email alerts
|

High fibrinogen‐to‐albumin ratio is associated with hemorrhagic transformation in acute ischemic stroke patients

Abstract: Introduction Hemorrhagic transformation (HT) is a complex and multifactorial complication among patients with acute ischemic stroke (AIS), and the inflammatory response has been considered as a risk factor for HT. We aimed to evaluate the stratification of FAR (fibrinogen‐to‐albumin ratio), an inflammatory biomarker, in HT patients. Methods A total of 256 consecutive stroke patients with HT and 256 age‐ and gender‐matched stroke patients without HT were included in this study. HT during hospitalization was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…In this study, the FAR levels of patients with SAP were higher than patients with non-SAP (0.113 vs. 0.087, P < 0.001; Table 1 ). The FAR level of patients with hemorrhagic transformation (HT) was higher than the patients with non-HT after stroke in a previous study (8.60 vs. 10.29, respectively; Table 1 ) ( 36 ). This may be due to the inflammatory response caused by the occurrence of stroke.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the FAR levels of patients with SAP were higher than patients with non-SAP (0.113 vs. 0.087, P < 0.001; Table 1 ). The FAR level of patients with hemorrhagic transformation (HT) was higher than the patients with non-HT after stroke in a previous study (8.60 vs. 10.29, respectively; Table 1 ) ( 36 ). This may be due to the inflammatory response caused by the occurrence of stroke.…”
Section: Discussionmentioning
confidence: 83%
“…Inflammation and acute stress are important elements of the pathophysiology pathway of acute ICH and secondary brain injury [ 17 ]. The fibrinogen to albumin ratio, as an inflammatory serum biomarker, has been identified in several studies as a predictor of poor outcome and adverse events in patients with cardiovascular diseases, cancer, sepsis, and stroke [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The acute-phase protein fibrinogen is an important part of the coagulation cascade as well as an indicator of systemic inflammation [ 20 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fibrinogen to albumin ratio, as an inflammatory serum biomarker, has been identified in several studies as a predictor of poor outcome and adverse events in patients with cardiovascular diseases, cancer, sepsis, and stroke [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The acute-phase protein fibrinogen is an important part of the coagulation cascade as well as an indicator of systemic inflammation [ 20 , 26 , 27 ]. Castellanos et al reported an association of good outcome and low fibrinogen level in non-surgically treated patients with medium to large spontaneous ICH [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second explanation may be owing to the neuroprotective effect of high albumin and low LDH levels, which may indirectly influence the risk of SAP by improving the severity of stroke. Albumin is an important antioxidant that may exert neuroprotective effects on stroke through antioxidant activity and anti-inflammatory activity ( 23 ). Besides, albumin can reverse blood stagnation and thrombosis, which can help maintain the vascular patency after successful thrombolysis ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%